Protection of the right to marry under Article 12 of the European Convention for the Protection of Human Rights and Fundamental Freedoms - Vojvodić, Jovana (Glasnik Advokatske komore Vojvodine, 2020)
Starting with the 21st century, the European Court of Human Rights has changed the approach regarding interpretation of the right to marry protected under Article 12 of the European Convention on Human Rights. The new liberal attitude towards the content of this right has opened up opportunities for new categories of persons to enter into marriage and start a family. The question arises whether the European Court of Human Rights will continue with this trend of interpretation and what consequences could that cause for the international understanding of marriage and family.